Archaeosomal nanocarriers improve pharmacokinetics and bioavailability of vancomycin after oral administration - Sedlmayr, Viktor Laurin; Quehenberger, Julian; Wurm, David; Gynther, Mikko; Vieth, Rebecca; Dürr, Valerie; Gesse, Pascal; Spadiut, Oliver; Fricker, Gert; Uhl, Philipp (European journal of pharmaceutical sciences, 2025)
Vancomycin, a glycopeptide antibiotic, is typically administered intravenously (IV) for severe Gram-positive bacterial infections. While the oral route offers higher patient adherence, it is limited by poor mucosal transport, restricting its use to intestinal infections. To address these challenges, this study explores the encapsulation of vancomycin into archaeosomes -phospholipid-based nanocarriers incorporating archaeal lipids, which exhibit exceptional stability in the gastrointestinal environment and interact specifically with enterocytes. Previous work demonstrated that lipid nanocarrier formulations benefit from the incorporation of the archaeal lipid calditolglycerocaldarchaeol (GCTE), facilitating mucosal barrier penetration and increasing bioavailability in vivo. In this study, we investigated the effects of archaeal lipid extract (ALE) and purified caldarchaeol (GDGT) on the pharmacokinetics and oral bioavailability of vancomycin in male Wistar rats. Our findings reveal that archaeosomal formulations significantly increase systemic exposure by prolonging circulation time and enhancing plasma drug concentrations, combined with high biocompatibility. Notably, the oral bioavailability (as measured by the area under the curve, AUC) increased 9-fold with GDGT liposomes and 4-fold with ALE liposomes compared to free vancomycin. These results highlight the potential of archaeal lipid-based drug delivery systems to enable oral administration of therapeutics that are traditionally injection-only.